Ascites in the Puerperium in the Context of a Woman with Turner Syndrome Who Conceived through Assisted Reproductive Technology. (22nd October 2015) - Tsagkas, Nikolaos; Valasoulis, George; Zikopoulos, Konstantinos; Zerzi, Calliope; Mitselos, Ioannis; Koutoulakis, Ioannis; Tzampouras, Nikolaos; Stefos, Theodor
Abstract : The case is about a young female who delivered twins by caesarean section (CS). On the 4th postoperative day, she presented with ascites which was resistant to empirical antibiotic and diuretic treatment. The woman was affected by Turner syndrome (TS); she had a medical background of chronic use of hormonal medication since puberty and conceived through ART- (assisted reproduction techniques-) IVF-oocyte donation. It is important to exhibit high suspicion for clot formation in the hepatic vasculature during the puerperium, especially in the case of history of chronic hormone treatment. Ascites albumin gradient and Doppler values lead to the diagnosis of thrombosis and the administration of high doses of anticoagulants is considered to be fundamental.